(untitled) (ADVANCES IN MECHANICAL ENGINEERING AND TRANSPORT, 2021)
The study deals with the identification of key problems of transport logistics in the field of motor transport. The statistic data for the recent five years have helped to specify sustainable growth in the motor transportation; it proves that the motor transport is in demand on the cargo transportation market of Ukraine. It has been defined that current market conditions decelerates the process of transportation logistics development. Basic tendencies in the field of motor transport, caused by the changes in world economy due to COVID-19, have been analyzed. The research results show that the economic crisis provoked by COVID-19 pandemic has influences negatively the worldwide economy on the whole. In particular, motor transport has experienced negative impact of the coronavirus. The obtained results have made it possible to outline the prospects of further development of the Ukrainian transport logistics market. The carried out analysis has demonstrated a pessimistic pattern of the transport logistics development; however, it should be noted that despite all the obstacles, Ukrainian motor transport is increasing its transportation volumes. There will be still a long-time tendency of certain advantage of transportation-dispatch companies, having no own motor equipment, over other transportation companies on the national market. Certain methods to solve the identified problems have been proposed taking into consideration features of the cargo transportation market. Implementation of those methods will result in the accelerated cargo delivery with the least costs. Moreover, the encouraging prospects as for the transfer of production facilities of European countries from China closer to the market outlets bring certain hope for the involvement of foreign investment in the Ukrainian economy in general and transportation field in particular. The research results can be used by managers of transportation companies while planning the enterprise activities. Key words: transport logistics, road transport, pandemic, freight transportation, trends.